Editorial - Costa, Cecilia; Velardi, Andrea (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
With this special issue, we wanted to take a closer look at the subject of flourishing, as it is thematised within the framework of the social sciences, with the intention of offering a contribution and an interpretative key to the practical urgency of offering a transdisciplinary reflection, which puts the person at the centre as a reflective actor able to act in the world. The term human flourishing refers to the person’s ability to live the different circumstances in which human existence unfolds, making them fruitful. According to this perspective, the concept of flourishing does not define a momentary state of grace but an evolutionary path for the realisation of the person, which has as its ultimate horizon the successful outcome of existence seen as ‘whole’.